Comparison of Efficacy and Outcome of Tubeless with Standard Percutaneous Nephrolithotomy in Patient with Renal Stones - Ubaid-ur-Rahman, Nadir Hussain, Bibhushit Mahat, Sulochana Dahal, Muhammad Nazir (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the outcome and complications of standard PCNL with tubeless PCNL in terms of analgesia requirement, incidence of infection, post-operative perinephric urinary collection and post-operative hospital stay. Study Design: Randomized control trial Place and Duration of Study: Department of Urology, Lahore General Hospital Lahore from 1st March 2018 to 30th April 2019. Methodology: Ninety six patients fulfilling the inclusion criteria were randomly categorized into 2 groups; Group A where patients will undergo standard PCNL and Group B where patients will undergo tubeless PCNL. Post-operatively, patients were assessed for the requirement for analgesia, rate of infection, post-operative urinary leakage and hospital stay. Results: The mean duration of surgery had no significant difference between the two treatment groups; tubeless group was on average 51 minutes while the standard PCNL group was 55 minutes. No significant difference was observed in reduction of hematocrit values between the groups (4.9% vs 4.2%). Transfusions were not required in either group. The average post-operative duration of hospital stay was 2 days in group 1 and group 2 was 3 days with P<0.001. Conclusion: Tubeless PCNL is effective in patients with kidney stones and requires fewer analgesic drugs and shorter hospital stay, post-operative complications are almost the same in both groups with no significant difference. Key words: PCNL, Standard, Tubeless, Complications